2011
DOI: 10.1128/jvi.00443-11
|View full text |Cite
|
Sign up to set email alerts
|

M94 Is Essential for the Secondary Envelopment of Murine Cytomegalovirus

Abstract: The gene M94 of murine cytomegalovirus (MCMV) as well as its homologues UL16 in alphaherpesviruses is involved in viral morphogenesis. For a better understanding of its role in the viral life cycle, a library of random M94 mutants was generated by modified transposon-based linker scanning mutagenesis. A comprehensive set of M94 mutants was reinserted into the MCMV genome and tested for their capacity to complement the M94 null mutant. Thereby, 34 loss-of-function mutants of M94 were identified, which were test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
59
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(61 citation statements)
references
References 46 publications
2
59
0
Order By: Relevance
“…The UL16 chaperone hypothesis might also explain the difference in the location of the block to capsid egress between HSV (at the membrane) and human cytomegalovirus (23), murine cytomegalovirus (24), and murine gammaherpesvirus 68 (13), all of which have blocks prior to the transport of their capsids to membranes and are noninfectious as a result. In particular, these viruses may be more dependent on their UL16 homologs for the assembly of tegument proteins onto capsids than is HSV; if so, the misarranged molecules may obscure the sequences that are needed for transport to the membrane.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The UL16 chaperone hypothesis might also explain the difference in the location of the block to capsid egress between HSV (at the membrane) and human cytomegalovirus (23), murine cytomegalovirus (24), and murine gammaherpesvirus 68 (13), all of which have blocks prior to the transport of their capsids to membranes and are noninfectious as a result. In particular, these viruses may be more dependent on their UL16 homologs for the assembly of tegument proteins onto capsids than is HSV; if so, the misarranged molecules may obscure the sequences that are needed for transport to the membrane.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, studies of several UL16 homologs have revealed defects in virion production when they are absent. In particular, in the cases of human cytomegalovirus (23), mouse cytomegalovirus (MCMV) (24), and murine gammaherpesvirus 68 (13), electron microscopy of null mutants revealed that capsids were not associated with membranes, and hence, no enveloped virions were seen. However, these studies suggest that the block to virion production occurs prior to transport to the membrane for mutant viruses.…”
mentioning
confidence: 99%
“…Although their interaction is also conserved (7,10,11,13,27,31), its functional significance remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…UL16 is found in both the nucleus and cytoplasm of infected cells (51,55,58), but a stable association with capsids has been found only in the cytoplasm (51). UL16-null mutants have a 10-fold reduction in virus titers (3,35), and for various other herpesviruses, such mutants have defects in cytoplasmic budding, based on the accumulation of capsids in the cytoplasm (24,48,61). Curiously, the UL16-capsid interaction is weakened within extracellular virions (51), indicating that tegument assembly is a dynamic process.…”
mentioning
confidence: 99%
“…UL16 is a 373-aa tegument protein that is also conserved among all herpesviruses (24,34,48,55,58,73). It contains 20 cysteines (51, 75), 8 of which are conserved.…”
mentioning
confidence: 99%